(untitled) (Information Horizons: American Journal of Library and Information Science Innovation (2993-2777), 2024)
The purpose of this study is to determine the most effective and cost-effective options for the traction electric drive system for the Tashkent metro. The work examines factors such as energy efficiency, reliability, availability, technical characteristics, economic aspects and environmental sustainability. The study is conducted by comparing different electric traction drive systems based on their energy efficiency, reliability, technical parameters, costs and environmental sustainability. The results obtained will allow us to identify the most optimal solutions for the Tashkent metro, taking into account its features and requirements